Pulmonary Tuberculosis Presenting as Acute Respiratory Failure and Unilateral Complete Lung Collapse: Two Case Reports With Review of Literature - Deependra Kumar Rai; Vatsal Bhushan Gupta; Priya Sharma; Ameet Harish (European Medical Journal, 2023)
Massive haemoptysis, which can result in abrupt respiratory failure, is a potentially fatal consequence of pulmonary tuberculosis. Radiologically, it can present as a complete collapse of one lung due to endobronchial clot formation. Here, the authors report two cases, one of whom was a female who was pregnant and near term, who presented with massive haemoptysis followed by severe respiratory distress. Fibre optic bronchoscopy was performed in both cases, and clots were retrieved. One of the patients required intubation and invasive mechanical ventilation. The procedure was technically difficult because of the acute hypoxaemia, necessitating a team of pulmonologists and anaesthetists. Bronchoalveolar lavage enabled the authors to clinch the diagnosis. Post-procedure, both patients showed rapid clinical and radiological improvement. In resource-limited settings where rigid bronchoscopy is not available, fibre optic bronchoscopy can be performed for clot retrieval, as it can be a life-saving procedure for the patient.